The role of the armed forces in homeland security - Marsili, M. (XI Congresso Português de Sociologia, Resumos de comunicações, 2021)
This poster addresses the employment of the Armed Forces in homeland security tasks. Unconventional conflicts – hybrid, asymmetric, and transnational conflicts which involve state and non-state actors such as insurgents or terrorist organizations – are among the trend topics of defense and security. Since jihadist terrorism broke out in in Europe, security has become a main concern, occupying the front pages of newspapers and the agendas of governments. Therefore, the debate on the employment of the Armed Forces in homeland security tasks became central. The primary responsibility for protecting life and property and maintaining law and order in the civilian community is vested in police forces; supplementary responsibility is vested by statute in specific agencies other than the Ministry of Defense. Military forces may be used to support law enforcement agencies. In emergency situations, the Parliament may authorize the use of the military as a police force on home soil. Police departments are much larger in major metropolitan areas and much smaller than the average in rural areas, but in catastrophic attacks that affect large areas in several states simultaneously, there will not be enough police officers to do what has to be done. Since lateral reinforcement is not feasible when all adjacent areas are involved, the only source of augmentation for local departments will be from the Armed Forces. Subsidiary operations of the Amy in support to civil authorities – e.g. military aid in the event of a catastrophe – are one of the ordinary duties of the Army, whose main mission is to ensure security and defense of the territory. Although the readiness of use for the defense of the territory is reduced, the maintenance and development of this important primary mission is to guard the long-term, in anticipation of events imponderables in the military and security policy. In Western liberal-democracies the executive power is limited in the use of the military in domestic security operations because of legal norms. Police is in charge of internal security, with the Army acting as ‘reinforcing force’ only in conjunction with the first. Subsidiary operations of the Army in the field of homeland security have increased over the past few years and in many countries is currently underway a political debate to evaluate the allocation of the Army direct powers in policing. It is a political decision, which must take into account both the changing environment in which the Armed Forces operate and the threat of international terrorism manifested in disruptive manner at the beginning of the new millennium. Legislative and cultural obstacles should be overcome to achieve this goal.